The role of digitalization of transfer pricing in the company’s management accounting system - Poyda-Nosyk Nina; Pojda-Noszik Nina; Пойда-Носик Ніна; Valentyna Borkovska; Борковська Валентина; Robert Bacho; Bacsó Róbert; Бачо Роберт; Gabriella Loskorikh; Loszkorih Gabriella; Лоскоріх Габріелла; Veronika Hanusych; et al. (Online Academic Press, 2023)
Abstract. The aim of the article was to study the theoretical and methodological aspects of the use of digital technologies in transfer pricing for the collection of the information background for management accounting. The study involved methods, such asthecalculation of financial indicators, methods of finding separate data and their synthesis, system analysis, grouping,and ranking.These methodsallowed for thecalculation ofthe coefficient of innovation and technical business developmentin 27 countries of the European Union.The data obtained allowed us to determine the effectiveness of digitalization of transfer pricing by different methods,depending on the stage of the product life cycle,and to show the impact on the company’s financial performance.Return on Equity and Return on Assets are directly affected by transfer pricing in companies of selected sectors of the economy. In conclusion,74% of the respondents noted positive changes in the financial result after the introduction of digital technologies in transfer pricing when making management decisions. The study will be useful for managers of different levels to convince them of the need for the digitalization of business processes. A promising area of further research is determining the impact of transfer prices on the overall state of tax payments of businesses.
Редакційний штат: https://onlineacademicpress.com/index.php/IJAEFA/about/editorialTeam Зміст: https://onlineacademicpress.com/index.php/IJAEFA/issue/view/73
Keywords: business processes; digital technologies; management decisions; profitability; transfer pricing